Implementasi Projek Penguatan Profil Pelajar Pancasila Dikelas IV SD Negeri 2 Bojongsari - Amalia Novitasari (J-SES : Journal of Science, Education and Studies, 2024)
The Pancasila Student Profile Project is the development of students' understanding of the profile of Pancasila students. according to the results of the author's interviews and observations with the fourth grade teacher of SD Negeri 2 Bojongsari, the author found a phenomenon related to the implementation of P5 activities at SD Negeri 2 Bojongsari. This research uses descriptive qualitative methods. The subjects in this study were the principal, fourth grade teacher, and fourth grade students of SD Negeri 2 Bojongsari. This research was conducted at SD Negeri 2 Bojongsari, Kembaran District, Banyumas Regency which was held from February to April 2024. Data collection methods in this study used interview techniques, observation, documentation and peer assessment. In this study, the data validity techniques used were source and technique triangulation techniques. The results of this study indicate that the implementation of the project activities to strengthen the profile of Pancasila students starts from planning, implementation, evaluation, and supporting and inhibiting factors of the project activities to strengthen the profile of Pancasila students in class IV SD Negeri 2 Bojongsari. The activity goes through several steps starting from the first planning, forming a team of facilitators, identifying the readiness of education units, determining dimensions, themes and time allocations and compiling project modules. The second is the implementation of the Pancasila student profile project activities, at SD Negeri 2 Bojongsari, especially in class IV, has implemented the project activities.